Leaching of mercury from seal carcasses into Antarctic soils - Zvěřina, O.; Coufalík, P. (Pavel); Brat, K.; Červenka, R.; Kuta, J.; Mikeš, O.; Komárek, J. (Environmental Science and Pollution Research, 2017)
This work focuses on the extent of the mercury input from seal carcasses and shows that such carcasses represent locally significant sources of mercury and methylmercury for the environment.